Effects of Different Surface Treatment Methods and Zirconia Primers on Shear Bond Strength of Orthodontic Brackets to Zirconium - Farahani, Mohammad; Kabiri, Sattar; Talebi Rafsanjan, Katayoun (Journal of Dental School, 2022)
Objectives Providing a reliable attachment between the bracket base and zirconia surface is a prerequisite for exertion of orthodontic forces. The purpose of the present study was to evaluate the effect of two surface treatment methods and three primers on shear bond strength (SBS) of orthodontic brackets to zirconia surface. Methods Zirconia blocks were milled and embedded in acrylic resin. The polished zirconia surfaces were randomly prepared with sandblasting (SB) and Er:YAG laser application (LA). Each group of 45 (SB and LA) was further divided into 3 subgroups of 15. The subgroups received different primers namely Z-Prime Plus, MKZ primer and Clearfil SE Bond Primer. The SBS values were measured and compared using two-way ANOVA. SPSS 21 for Macintosh was used for all statistical analyses. Level of significance was set at P<0.05. Results The SB group exhibited a mean SBS of 14.393 MPa, which was significantly higher than the mean SBS recorded for LA group (5.683 MPa; P<0.05). In SB subgroups, there was no significant difference among the primers in SBS (P= 0.391), but this was not the case for laser subgroups (P< 0.05) and the subgroups that received Clearfil SE and Z-Prime Plus had higher SBS than the MKZ primer subgroup. Conclusion This study suggests that simultaneous use of sandblasting and primers containing 10-methacryloyloxydecyl dihydrogen phosphate (MDP) monomer can result in acceptable SBS of brackets to zirconia surfaces.